2013
DOI: 10.1002/ptr.4957
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐biofilm Effects of Honey Against Wound Pathogens Proteus mirabilis and Enterobacter cloacae

Abstract: Biofilm growth and its persistence within wounds have recently been suggested as contributing factors to impaired healing. The goal of this study was to investigate the anti-biofilm effects of several honey samples of different botanical origin, including manuka honey against Proteus mirabilis and Enterobacter cloacae wound isolates. Quantification of biofilm formation was carried out using a microtiter plate assay. All honeys at a sub-inhibitory concentration of 10% (w/v) significantly reduced the biofilm dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…The plates were incubated in an orbital shaker (1500 r.p.m.) at 37 uC for 24 and 48 h. After incubation, the biofilm formation was measured using a crystal violet staining method according to our previous study to detect polymeric substances (Majtan et al, 2014). The viability of biofilm-forming cells was measured using resazurin according to van den Driessche et al (2014).…”
Section: Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The plates were incubated in an orbital shaker (1500 r.p.m.) at 37 uC for 24 and 48 h. After incubation, the biofilm formation was measured using a crystal violet staining method according to our previous study to detect polymeric substances (Majtan et al, 2014). The viability of biofilm-forming cells was measured using resazurin according to van den Driessche et al (2014).…”
Section: Pcrmentioning
confidence: 99%
“…A few studies have attempted to identify the active compounds responsible for the antibiofilm activity of honey (Truchado et al, 2009;Lee et al, 2011;Majtan et al, 2014). Most of these compounds take part in the prevention of biofilm formation, but little information is available regarding compounds that are able to disrupt established wound biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-biofilm property of the honey was attributed to methylglyoxal. 38 Currently, anti-biotic use poses a well established impediment, due to the emergence of resistant bacteria. On the other hand, due to multi-phytochemical composition and the array of differing anti-microbial mechanisms, manuka honey seems well presented to inhibit even antibiotic-resistant 'superbugs'.…”
Section: Anti-bacterial Anti-biotic and Anti-viral Effectsmentioning
confidence: 99%
“…Similar to our finding, Alandejani et al [47] by using Sidr and Manuka honeys reported that biofilm-producing strains of P. aeruginosa were more susceptible to inhibitory effect of honey samples than S. aureus strains. According to study of Majtan et al [48], it has been suggested that methylglyoxal, an antibacterial compound of Manuka honey, is responsible for killing biofilm-embedded wound bacteria. However, further studies are necessary to determine the mechanism by which honey prevents biofilm formation.…”
Section: Discussionmentioning
confidence: 99%